ANALISIS UNSUR INTRINSIK PADA NOVEL “LAYAR TERKEMBANG” KARYA SUTAN TAKDIR ALISJAHBANA - Yanastasia Heni; A.A. Rai Laksmi; I Nyoman Diarta (JIPBSI (Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia), 2022)
This research is a qualitative descriptive study. The main purpose of this research is to provide an overview and also knowledge to readers or literary connoisseurs about the intrinsic elements contained in the novel Layar Terkembang by Sutan Takdir Alisjahbana. The data in this study is the text of the novel Layar Terkembang by Sutan Takdir Alisjahbana. The instruments used in this research are the researcher himself and the data card. The data collection technique in this research is using reading and note-taking techniques. The data analysis method in this study used a qualitative descriptive technique. The results of this study indicate the findings of intrinsic elements, namely the theme, plot, characters and characterizations, setting, language style, point of view and mandate. The theme found in this novel is about women's emancipation and romance. The flow used is the forward flow. The main characters are Tuti, Maria and Yusuf; supporting characters, namely Raden Wiriaatmaja, Partadiharja, Saleh, Ratna, Sukarto and Rukamah; while the side characters are the three boys around the aquarium, Partadiharja's wife, Juhro, Yusuf's father, Yusuf's mother, Dahlan, Rukmini, nurse Maria, Iskandar and Ningsih. The setting is at the Fish Market, near a shady tamarind tree, under a mango tree, consensus building, front porch, Lake Ranau, polyclinic, Martapura City, Dago Waterfall, CBZ (hospital), Saleh's house in Sessionlaya, at home sick in Pacet and public cemeteries; the time setting occurs in the morning, afternoon, evening and Sunday; The background of the atmosphere is bustling, wisdom, serenity and emotion. The language style used is using figurative language (personification, hyperbole and litotes) and ancient Malay language. The point of view used is the third person point of view. The mandate is that women must be knowledgeable in order to have a great influence in the life of the nation and state so that their position in society can be more respected.